Analisis Location Quotient (LQ) dalam Penentuan Wilayah Basis dan Arah Pengembangan Sapi Perah di Daerah Istimewa Yogyakarta - Meita Puspa Dewi; Marosimy Millaty; Marlianasari Putri; Nur Saudah Al Arifa Dewi (Fakultas Pertanian - UMJ, 2026)
The objective of this research was to facilitate the advancement of livestock farming that is sustainable by employing a descriptive quantitative methodology. The data used are secondary data that are then tabulated, presented in the form of tables and images, and subsequently analyzed using the Location Quotient (LQ). The research results show that the basis for dairy cattle development is in Sleman Regency, while the non-basis areas are in Bantul Regency, Kulon Progo, Gunung Kidul, and Yogyakarta City. The strategy for developing the dairy cattle base areas is to focus on development in the base areas, ensure the sustainable availability of green fodder and concentrates, implement local government policies, develop livestock groups to enhance knowledge, and have supporting institutions that collaborate. Recommendations require further research on the macro and micro potential in each region.